INOVASI MAGGOT (Larva Black Soldier Fly) FERMENTASI SEBAGAI PAKAN BENIH IKAN TOMAN (Channa micropeltes) - Rahmah Rahmah; Noor Arida Fauzana; Slamat Slamat (Universitas Lambung Mangkurat, 2023)
Toman fish is a pure carnivore fish which so far has used wild catches as its entire diet. Alternative feed with high animal protein and easy to obtain needs to be done. Fermentation activities using tempe yeast can usually increase the protein content of a material. Studies on the use of fermented maggot for toman fish seed feed have not yet obtained sufficient information, so in-depth research on this matter really needs to be done. This study aims to analyze the nutritional content of fermented maggot on the growth of toman fish. Observations were made for 60 days with A1B1 treatment (Maggot + 0% Rhizopus sp). A1B2 (Maggot+5% Rhizopus sp), A1B3(Maggot+10% Rhizopus sp), A2B1(Maggot pres+0% Rhizopus sp), A2B2 (Maggot pres+5% Rhizopus sp), and A2B3 (Maggot pres+10% Rhizopus sp.). Parameters measured were maggot nutritional content, as well as growth, survival, feed efficiency, protein retention and fat retention in toman fish. The best research results showed that the nutritional content of maggot with the highest protein was found in the A2B3 treatment (Maggot pres + 10% Rhizopus sp) while the best growth and feed efficiency were found in the A2B2 treatment (Maggot pres + 5% Rhizopus sp). The nutritional content of maggot feed which was treated with fermentation using tempeh yeast could increase the protein content of maggot and after it was given to the toman according to the treatment it showed an increase in growth in each treatment.